Left Behind, At Risk, and Vulnerable Elders in Rural China: What the RUMIC Data Reveal about the Extent, Causes, and Consequences of Being Left Behind - Rachel Connelly; Margaret Maurer-Fazio (Institute for the Study of Labor (IZA), 2015)
Migration of any distance separates family members for long periods of time. In China, an institutional legacy continues to privilege the migration of working-age individuals who often leave children and elders behind in the rural areas. Up to now, the literature has treated children and elders analogously, labeling each group "left-behind". We argue that analysis of elder stayers needs to be more nuanced, distinguishing among differing groups of elders. Of these groups, those living alone without any adult children in the village are most at risk of negative consequences of migration, while those living with other non-migrant children are much less affected by migration. We find evidence, when focusing on the consequences of migration on elders, that an elder-centric analysis is preferable to a migrant-child-centric analysis.
Keywords: J12; J14; J21; J26; O53; 330; living arrangements; aging; China; rural; elderly; left behind; at risk; migration